Evaluation of four surgical implantation techniques for age‐0 white sturgeon (Acipenser transmontanus Richardson, 1836) with a new acoustic transmitter. (11th December 2017) - Liss, S. A.; Ashton, N. K.; Brown, R. S.; Walker, R. W.; Bates, P.; Klassen, C.; Backhouse, S.
Summary: The goal of this study was to evaluate four implantation techniques by assessing transmitter retention, survival, growth, and wound healing responses in white sturgeon ( Acipenser transmontanus Richardson, 1836). A new acoustic transmitter (AT; cylindrical, 0.7 g in air, 24.2 × 5.0 mm, up to 365 days battery life) was developed to monitor age‐0 sturgeon; however, an implantation technique is critical to provide guidance for its use in field research. Sturgeon ( n  =   150, 182–289 mm fork length, 35–116 g) were separated into five treatments ( n  =   30 per treatment): (i) control, (ii) flank incision with one suture, (iii) flank incision without a suture, (iv) offline incision with one suture, and (v) offline incision without a suture. Fish were implanted with a non‐functioning AT and observed for 28 days. Transmitter retention was 100% and only fish in the offline incision without a suture treatment had reduced growth (0.15% mm growth per day) compared to controls (0.38%) over the 28 days study. Suturing caused an increase in incision inflammation, ulceration, and water mold infection. Offline incisions were more susceptible to varicosities than flank incisions. Non‐sutured incisions showed greater incision openness, but only during the first 14 days post‐implantation. A flank incision without a suture is recommended for implanting this new AT in age‐0 white sturgeon.